PERANCANGAN RUANG SOSIAL BERBASIS BUDAYA CINA BENTENG SEBAGAI GENERATOR BARU PECINAN PASAR LAMA TANGERANG - Helen Rosabella Arianto; Suwardana Winata (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
Tangerang Old Market Chinatown is known as the forerunner to the birth of Chinatown in the Tangerang area whose descendants are now better known as Cina Benteng. Chinatown which has existed since 3 decades ago, of course, has a deep historical background, but over time and the development of the era, Tangerang Old Market Chinatown is forced to continue to follow the rapid development of Tangerang City. Without realizing it, Tangerang Old Market Chinatown is gradually began to experience changes in form, function, a decrease in environmental quality that had an impact on the social life of the people in the Chinatown of Pasar Lama Tangerang. Through the acupuncture system by piercing the deep parts that require improving the quality of life in the community, as well as by observing the daily activities of the people in Chinatown. The collected data, observation and analysis will be used as the basis for the development of social space in Tangerang Old Market Chinatown, with the main focus on developing Cilame Street. The formation of social space from the culture and daily life of the Chinese Benteng community in Tangerang's Old Market Chinatown can support the creation of increased social interactions that occur in Chinatown communities, as well as the injection of culinary functions in the building can restore the characteristics of Chinatown through cultural culinary, and also this development will be act as a new generator for Chinatown Tangerang Old Market to introduce the culture of the Chinese Benteng community and indirectly can become an attraction for the surrounding community and newcomers to come to Tangerang Old Market Chinatown. Keywords: Attractor; Cultural Culinary; Local Identity; Social Space Abstrak Pecinan Pasar Lama Tangerang dikenal sebagai cikal bakal lahirnya pecinan di daerah Tangerang yang keturunannya saat ini lebih dikenal sebagai Cina Benteng. Pecinan yang telah ada sejak 3 dekade lalu tentunya telah memiliki latar belakang sejarah yang dalam, namun seiring dengan berjalannya waktu dan perkembangan jaman maka Pecinan Pasar Lama Tangerang terpaksa harus terus mengikuti arus perkembangan Kota Tangerang yang begitu pesat, sehingga tanpa disadari Pecinan Pasar Lama Tangerang lambat laun mulai mengalami perubahan bentuk, fungsi, penurunan kualitas lingkungan yang berdampak kepada kehidupan sosial masyarakat di Pecinan Pasar Lama Tangerang. Melalui sistem akupunktur dengan menusuk pada bagian yang dalam membutuhkan peningkatan kualitas hidup dalam masyarakat, serta dengan observasi kegiatan keseharian masyarakat dalam pecinan, dapat menjadi dasar pengembangan ruang sosial pada Pecinan Pasar Lama Tangerang dengan focus utama pengembangan pada Jalan Cilame. Pembentukan ruang sosial dari budaya dan keseharian masyarakat Cina Benteng dalam Pecinan Pasar Lama Tangerang dapat mendukung terciptanya peningkatan interaksi sosial yang terjadi dalam masyarakat pecinan, serta dengan adanya injeksi fungsi kuliner dalam bangunan dapat mengembalikan karakteristik pecinan melalui kuliner budaya, juga dapat menjadi generator baru bagi Pecinan Pasar Lama Tangerang untuk mengenalkan budaya masyarakat Cina Benteng dan secara tidak langsung dapat menjadi atraktor bagi masyarakat sekitar dan pendatang untuk datang ke Pecinan Pasar Lama Tangerang.